Effectiveness of the tools and techniques used for the marketing of supply chain finance products of IDLC - Joya, Nowsheen Anjum (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.